AN EMPIRICAL ANALYSIS OF FIRM-SPECIFIC DETERMINANTS OF CAPITAL STRUCTURE BEFORE AND DURING COVID-19: EVIDENCE FROM HOTEL, RESTAURANT AND TOURISM INDUSTRIES IN INDONESIA - Qanita Noviandy, Rashifa
Capital structure is important to any business since it affects the financial choices of the firm. Combining debt and equity provides the foundation of the business's capital structure and is utilized to finance the entire operations and growth of the organization. The business's ultimate aim is to properly mix the debt-to-equity ratio to maximize shareholder value while reducing capital costs, preventing the company from possible risks such as bankruptcy and financial distress. When the Covid-19 pandemic was formally declared in early March 2020, severe negative impacts impacted almost all Indonesian industry sectors. Hotel, restaurant and tourism are regarded one of the most severely impacted sectors of business. This pandemic has certainly decreased the amount of resources that businesses may acquire, collect, and utilize to thrive, given sluggish economic growth and no capital inflow. The aim of this research study is to examine the impacts of firm-specific characteristic capital structure development among a sample of 26 hotel, restaurant and tourist businesses listed on the Indonesia Stock Exchange (IDX) in the second and third quarters of 2019 and 2020. The nature of these businesses needs a significant amount of money to invest, these companies' financing choices become more crucial. Using the random-effects model to test the hypotheses, this study found that asset tangibility, tax shield, and earnings volatility are significantly associated with book leverage. Tax shield and earnings volatility are significantly associated with debt to equity. size and earnings volatility are significantly associated with net equity.